Investigation of fumonisin interaction with maize macrocomponents and its bioaccessibility from porridge using the dynamic tiny-TIM gastrointestinal model. (July 2020) - du Plessis, Belinda; Regnier, Thierry; Combrinck, Sandra; Steenkamp, Paul; Meyer, Hannalien
Abstract: Contamination of maize by fumonisin mycotoxins is of major concern to consumer health. This study was designed to improve our understanding of the binding of fumonisin B (FB) to maize and its major macrocomponents, during the preparation of porridge. None of the processing treatments (pH 4, 7 and 10) or temperatures (30 and 90 °C) used resulted in a significant decrease in the recovery of FB1 from spiked starch, zein or maize meal. These results confirm the stability of FB1 in maize porridge, and the absence of modified forms of FB. The bioaccessibility of fumonisins in the gastrointestinal tract, following consumption of contaminated stiff maize porridge, was determined using the TNO Gastrointestinal Model (tiny-TIM). The porridge was digested in the tiny-TIM using parameters simulating human digestion. The concentrations of fumonisins were determined in the dialysates at fixed time intervals using ultra performance liquid chromatography-quadrupole Time-of-Flight high definition mass spectrometry (UPLC-QToF-HDMS). The results proved that fumonisins B1, B2 and B3 are released rapidly from stiff porridge prepared from contaminated maize meal. This confirms that the low bioavailability of fumonisins cannot be attributed to strong association of the toxin with the intestinal content. This study presents new insights into the stability of fumonisins in maize porridge and the kinetics of fumonisin-release from porridge through simulated human digestion, suggesting that consumers using maize as a staple may be at risk. Highlights: Stability of FB1 in maize porridge was confirmed. Fumonisins are released rapidly from contaminated stiff maize porridge. After 360 min, 68–94% of the fumonisins were bioaccessible.